2018
DOI: 10.3389/fpsyt.2018.00116
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making in Suicidal Behavior: The Protective Role of Loss Aversion

Abstract: BackgroundLoss aversion is a central and well operationalized trait behavior that describes the tendency for humans to strongly prefer avoiding losses to making equivalent gains. Human decision-making is thus biased toward safer choices.AimThe aim of this study was to explore the relationship between loss aversion and suicidal behavior in a large cohort of adolescents recruited in 30 schools of seven European countries for a longitudinal study (Current Controlled Trials ISRCTN65120704). We hypothesized that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 80 publications
2
25
3
3
Order By: Relevance
“…The study population consisted of 2046 adolescents (mean age 15.34±1.01; 56.3% females) who participated in the longitudinal SUPREME (Suicide Prevention through Internet and Media Based Mental Health Promotion) project between 2012 and 2013 [12,13]. These pupils were recruited from 27 randomly selected schools in six European countries, namely Estonia (West Viru County), Hungary (Budapest), Italy (Molise), Spain (Barcelona), Sweden (Stockholm County), and the United Kingdom (eastern England).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consisted of 2046 adolescents (mean age 15.34±1.01; 56.3% females) who participated in the longitudinal SUPREME (Suicide Prevention through Internet and Media Based Mental Health Promotion) project between 2012 and 2013 [12,13]. These pupils were recruited from 27 randomly selected schools in six European countries, namely Estonia (West Viru County), Hungary (Budapest), Italy (Molise), Spain (Barcelona), Sweden (Stockholm County), and the United Kingdom (eastern England).…”
Section: Study Populationmentioning
confidence: 99%
“…During the study, the participants were allocated to three different groups in order to evaluate a mental-health promoting website [12]. Further details about SUPREME's sample and procedures are available in previous publications [12,13]. All the pupils participating in SUPREME with available age and sex, and who responded to baseline questions about their sexual orientation and serious suicidal ideation, were included in this study.…”
Section: Study Populationmentioning
confidence: 99%
“…[8][9][10][11] Studies have used different self-report methods to assess participants' behaviors after completing MHFA training, such as confidence, intentions, and help provided. [8][9][10][12][13][14][15][16][17] However, research on observed performance is lacking. Psychologists have noted the shift from direct observation to "introspective self-reports, hypothetical scenarios and questionnaire ratings" to measure self-reported behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The program also educates the public on how to refer individuals in need of care to the appropriate providers. A metaanalysis of this program indicated that participants in the program increased their knowledge about mental health and increased their own supportive behavior toward individuals with mental health issues (Hadlaczky, Hökby, Mkrtchian, Carli, & Wasserman, 2014). The MHFA, or similar-type program, is easily translatable between community organizations and in the workplace.…”
Section: Study Summary and Implicationsmentioning
confidence: 99%